Styrofoam-and-Velcro: An Alternative to Ball-and-Stick Models - Sawyer R. Masonjones (American Society for Microbiology, 2014)

(untitled)
For students learning biology at introductory levels, one of the most significant instructional barriers is their lack of preparation in chemistry. In upper-division college chemistry and biology courses, students employ ball-and-stick models in order to visualize molecular structures, but at the introductory biology level, models are inconsistently used and at the secondary level they are avoided altogether. Traditional ball-and-stick models perform poorly at all levels because they only show bonds, never valence electrons. This poses a problem for students who are visual or kinesthetic learners, as modeling electrons in the bonding process may be critical to understanding the mechanisms behind the biochemical reactions that serve as a foundation for biological concepts. Our molecular modeling kits show the action of valence electrons and correctly deal with the issue of polarity and partial charge, while still illustrating structure and function similarly to ball-and-stick models, allowing students to model nearly every reaction or molecule they may need to learn. Additionally, this kit will foster model building exercises required as part of the Next Generation Science Standards (http://www.nextgenscience.org/next-generation-science-standards). This model was devloped in conjunction with 'Molecular Twister: A Game for Exploring Solution Chemistry' (JMBE Vol 15, No 1; http://jmbe.asm.org/index.php/jmbe/article/view/652) by the same authors, which uses principles derived from the present paper.